2002
DOI: 10.1590/s0004-27302002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Densidade Mineral Óssea: Estudo Transversal em Pacientes com Síndrome de Turner

Abstract: A síndrome de Turner (ST) caracteriza-se pela perda parcial ou total de um dos cromossomos X, hipogonadismo hipergonadotrófico e baixa estatura. A maioria dos estudos de densidade mineral óssea (DMO) em ST atribuem a osteoporose à ausência do desenvolvimento puberal e ao hipoestrogenismo, enquanto o envolvimento das alterações ósseas intrínsecas à ST permanece obscuro. O objetivo deste estudo foi verificar a associação entre a DMO com as variáveis como idade cronológica e óssea, peso, altura, cariótipo, doença… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…16 Although some studies have already demonstrated a positive relationship between weight and BMD, 22,23,24 in our study with BMI, no difference was observed between groups with higher or lower BMI values. These findings are similar to those of Costa et al 19 Alghadir et al 13 estimate a variation in bone mineral density (BMD) from 60% to 80%, that is influenced not only by ethnic and genetic factors, but also by modifiable environmental factors such as adiposity, hormone levels, sun exposure, blood pressure, physical activity, and diet. Body weight is a factor that would have a positive influence on BMD, although this relationship is not linear, as even in obese patients, BMD can be compromised.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…16 Although some studies have already demonstrated a positive relationship between weight and BMD, 22,23,24 in our study with BMI, no difference was observed between groups with higher or lower BMI values. These findings are similar to those of Costa et al 19 Alghadir et al 13 estimate a variation in bone mineral density (BMD) from 60% to 80%, that is influenced not only by ethnic and genetic factors, but also by modifiable environmental factors such as adiposity, hormone levels, sun exposure, blood pressure, physical activity, and diet. Body weight is a factor that would have a positive influence on BMD, although this relationship is not linear, as even in obese patients, BMD can be compromised.…”
Section: Discussionsupporting
confidence: 87%
“…18 In our study, the two groups of karyotypes (45,X and karyotypes with mosaicism) were compared and no differences were found regarding the Z-score for height, BMI and BD results, which is in agreement with the literature. 16,19,20 Short stature in TS can be largely attributed to the haploinsufficiency of the SHOX gene, which has been correlated with short stature and bone phenotype in TS. 3,16,20,21 There are studies that describe an increased risk of fractures associated with the syndrome, however with an inconclusive relationship with BD, 5,12,21 since they present normal BD Z-score values after correction for HA, although clinically they present an increased risk for fractures.…”
Section: Discussionmentioning
confidence: 99%